Belimumab in kidney transplantation: an experimental medicine, randomised, placebo-controlled phase 2 trial. Issue 10140 (30th June 2018) - Banham, Gemma D; Flint, Shaun M; Torpey, Nicholas; Lyons, Paul A; Shanahan, Don N; Gibson, Adele; Watson, Christopher J E; O'Sullivan, Ann-Marie; Chadwick, Joseph A; Foster, Katie E; Jones, Rachel B; Devey, Luke R; et al.
Summary: Background: B cells produce alloantibodies and activate alloreactive T cells, negatively affecting kidney transplant survival. By contrast, regulatory B cells are associated with transplant tolerance. Immunotherapies are needed that inhibit B-cell effector function, including antibody secretion, while sparing regulators and minimising infection risk. B lymphocyte stimulator (BLyS) is a cytokine that promotes B-cell activation and has not previously been targeted in kidney transplant recipients. We aimed to determine the safety and activity of an anti-BLyS antibody, belimumab, in addition to standard-of-care immunosuppression in adult kidney transplant recipients. We used an experimental medicine study design with multiple secondary and exploratory endpoints to gain further insight into the effect of belimumab on the generation of de-novo IgG and on the regulatory B-cell compartment. Methods: We undertook a double-blind, randomised, placebo-controlled phase 2 trial of belimumab, in addition to standard-of-care immunosuppression (basiliximab, mycophenolate mofetil, tacrolimus, and prednisolone) at two centres, Addenbrooke's Hospital, Cambridge, UK, and Guy's and St Thomas' Hospital, London, UK. Participants were eligible if they were aged 18–75 years and receiving a kidney transplant and were planned to receive standard-of-care immunosuppression. Participants were randomly assigned (1:1) to receive either intravenous belimumab 10 mg per kg bodyweight or placebo, given at day 0, 14, and 28, and then every 4 weeks for a total of seven infusions. The co-primary endpoints were safety and change in the concentration of naive B cells from baseline to week 24, both of which were analysed in all patients who received a transplant and at least one dose of drug or placebo (the modified intention-to-treat [mITT] population). This trial has been completed and is registered withClinicalTrials.gov, NCT01536379, and EudraCT, 2011–006215–56. Findings: Between Sept 13, 2013, and Feb 8, 2015, of 303 patients assessed for eligibility, 28 kidney transplant recipients were randomly assigned to receive belimumab (n=14) or placebo (n=14). 25 patients (12 [86%] patients assigned to the belimumab group and 13 [93%] patients assigned to the placebo group) received a transplant and were included in the mITT population. We observed similar proportions of adverse events in the belimumab and placebo groups, including serious infections (one [8%] of 12 in the belimumab group and five [38%] of 13 in the placebo group during the 6-month on-treatment phase; and none in the belimumab group and two [15%] in the placebo group during the 6-month follow-up). In the on-treatment phase, one patient in the placebo group died because of fatal myocardial infarction and acute cardiac failure. The co-primary endpoint of a reduction in naive B cells from baseline to week 24 was not met. Treatment with belimumab did not significantly reduce the number of naive B cells from baseline to week 24 (adjusted mean difference between the belimumab and placebo treatment groups −34·4 cells per μL, 95% CI −109·5 to 40·7). Interpretation: Belimumab might be a useful adjunct to standard-of-care immunosuppression in renal transplantation, with no major increased risk of infection and potential beneficial effects on humoral alloimmunity. Funding: GlaxoSmithKline.